Analisis Metode Pembelajaran Sejarah Kebudayaan Islam dalam Meningkatkan Minat Belajar Siswa - Anisa Fadillah; Maharani Maharani; Fara Fazira Ihsan (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2023)
The history of Islamic culture is a subject that presents stories of Islam in the past. The history of Islamic culture is often considered less interesting because of its monotonous learning process. So it is important to choose the right learning method so that the learning atmosphere is more active and interesting so that students' learning interest increases. This study aims to find out the various Islamic Culture Seharah learning methods that are appropriate in increasing students' understanding and character because the methods applied in the learning process play a role in improving the quality of learning and increasing student learning interest. The research approach used is the study of literature and references used in the form of books, journals, articles and scientific papers. The results showed that the appropriate learning methods for the history of Islamic culture in increasing students' interest in learning were direct learning methods, group presentation methods, and mind mapping methods.